Pleiotropic Effects of Metformin on the Antitumor Efficiency of Immune Checkpoint Inhibitors - Liu, Wenhui; Wang, Ying; Luo, Jianquan; Liu, Mouze; Luo, Zhiying (Frontiers in Immunology, 2021)
Cancer has become one of the most important threats to public healthy because of the high morbidity and mortality. In recent decade, immune check inhibitors (ICIs) have ushered a new therapeutic era in clinical oncology. And the high speed development of immune check-point therapies were owing to their inspiring clinical efficacy in a group of cancer types. Metformin, an effective agent for the management of type 2 diabetes mellitus (T2DM), is evidenced as a beneficial effect on cancer prevention and an improvement in cancer treatment. Emerging studies suggested that metformin combined ICIs treatment could improve the anticancer effects of ICIs. Hence, we conducted a system review to summarize the effects of metformin on ICIs therapy and pleiotropic mechanisms of metformin combined ICIs in cancer therapy, including the direct and indirect effects of metformin on the host immune system.